Teacher Work Discipline Metaphor from The Perspective of High School Students: Implications for Improving Learning Achievement - Ayu Wulandari; Nunuk Hariyati; Amrozi Khamidi; Arifannisa; Mochamad Nashrullah; Hardianto (Journal of Educational Studies, 2026)
This study aims to analyze students' perceptions of teacher discipline and its relationship with learning achievement at the high school (SMA) level. Teacher discipline is one of the important factors that affect the learning process, where teacher discipline can set a positive example and create a conducive learning environment. This study uses a survey method by distributing questionnaires to students in several high schools in the Surabaya-East Java area randomly. The data was analyzed using the results of the validity test of the instruments filled in by students about teacher discipline and learning achievement. The results of the study show that most students have a positive perception of teacher discipline. Disciplined teachers are considered to be able to increase students' motivation and concentration in learning, which ultimately has a positive impact on learning achievement. In addition, it found an insignificant relationship between teacher discipline and learning achievement, where higher teacher discipline was less likely to correlate with better learning achievement. The conclusion of this study is that students' perception of teacher discipline does not have a significant influence on learning achievement at the high school level. Therefore, it is important for teachers to continue to understand the norms that exist in schools with teachers who actively teach in the classroom and learning activities to support students' academic achievement.